Effective Training for a Grueling Race - Roberson, D. (2001)
A Finnish study, cited in Owen Anderson`s Running Research News, identified the two major energy sources for running the 400. Anderson states, "As you plan your workouts, remember that muscles have two key ways to obtain energy during a 400: (1) Creatine phosphate itself generates energy, and (2) Glucose breaks down to form lactic acid." The study also showed creatine phosphate is depleted by almost fifty percent after only 100 meters and then slowly depletes almost completely by 400 meters. Creatine phosphate levels do not return to normal levels for a full eight minutes following the race. Therefore, it would make sense for 400 runners to do repeat 100s almost all out with five to eight minute recoveries. These jaunts will increase the muscles` ability to use creatine. Since the discovery that lactic acid levels were highest at about 300 meters, Anderson concluded that 300s, "do a fantastic job of maximizing muscles` ability to break down glucose. "200 meter sprints, however, were found to be inefficient for 400 training. The levels of creatine phosphate had already dropped in half at 100 meters, and the rate of glycolosis didn`t reach its peak until 300 meters. Unfortunately, 400 intervals with only three minutes rest (a workout only a complete masochist would enjoy) were found to be the best workout to build up muscular tolerance to acidity. Intervals over 400m were shown to be ineffective because creatine phosphate levels were too low for any real benefit. I hope that all of this hasn`t confused you. In essence the Finn`s research helped Anderson conclude that a good 400 training program needs the following: 1.100s run at close to full speed with full recoveries (5-8 minutes) 2.300s run at close to full speed with full recoveries (8 minutes or longer) 3.400s run at close to full speed with short recoveries (3 minutes) These guidelines offer quarter milers a scientific road map to design an effective workout program, but it is not written in stone anywhere that you should only run 100s, 300s and 400s while training. I briefly trained with the Santa Monica Track Club in college, and still incorporate workouts learned from Joe Douglas, the Santa Monica Track Club head coach, and John Smith, the UCLA head coach. They taught me to run 350s for time and then add 7 seconds early in the season and 6 seconds late in the season to get my equivalent 400 time. This technique allows you to run more relaxed in training, since you don`t have the final painful 50 meters of the 400 looming in the back of your mind.